Evaluation of the Implementation of Systems and Procedures for Spending Cash Supply at the Regional Revenue Agency of Bitung City - ARRAHMA, Almiftah; AFFANDI, Dhullo; WEKU, Priscilia (Journal of Governance, Taxation and Auditing, 2023)
Tax Good governance is reflected, among other things, in transparent and accountable government financial management. This study aims to evaluate the systems and procedures for disbursing cash at the Regional Revenue Agency of the city of Bitung, whether they refer to government regulation no. 12 of 2019 and what is the procedure for disbursing cash in stock money at the Regional Revenue Agency for the city of Bitung. This type of qualitative research uses a descriptive analysis method with a case study approach. The results of research on systems and procedures for spending money at the Regional Revenue Agency of Bitung City are by Government Regulation no. 12 of 2019, systems and procedures for disbursing cash (UP) have been supported by related documents such as Payment Orders (SPP), Payment Orders (SPM), and Funds Disbursement Orders (SP2D), and transaction documents to complete the inventory of cash procedures. The system for issuing Warrants for Payment of Supply Money (SPM-UP) at BAPENDA Bitung City, especially in preparing SPM-UP documents and examining supporting documents, their application is by the characteristics of regional financial management according to Government Regulation Number 12 of 2019. However, in practice, the issuance process is inappropriate because the operator is still handling it, and the PPK SKPD must carry out this task.